Fine mapping of 2q35 high‐risk neuroblastoma locus reveals independent functional risk variants and suggests full‐length BARD1 as tumor‐suppressor. Issue 11 (4th October 2018) - Cimmino, Flora; Avitabile, Marianna; Diskin, Sharon J.; Vaksman, Zalman; Pignataro, Piero; Formicola, Daniela; Cardinale, Antonella; Testori, Alessandro; Koster, Jan; de Torres, Carmen; Devoto, Marcella; Maris, John M.; et al.
Abstract : A previous genome‐wide association study (GWAS) identified common variation at the BARD1 locus as being highly associated with susceptibility to high‐risk neuroblastoma, but the mechanisms underlying this association have been not extensively investigated. Here, we performed a fine mapping analysis of BARD1 locus (2q35) using GWAS data from 556 high‐risk neuroblastoma patients and 2, 575 controls of European‐American ancestry, and identified two independent genome‐wide neuroblastoma‐associated loci. Functional single‐nucleotide polymorphism (SNP) prioritization identified two causative variants that independently contributed to neuroblastoma risk, and each replicated robustly in multiple independent cohorts comprising 445 high‐risk cases and 3, 170 controls (rs17489363: combined p = 1.07 × 10 −31, OR:1.79, 95% CI:1.62–1.98 and rs1048108: combined p = 7.27 × 10 −14, OR:0.65, 95% CI:0.58–0.73). Particularly, the T risk allele of rs17489363 in the canonical promoter region of full‐length BARD1 altered binding site of the transcription factor HSF1 and correlated with low expression of full‐length BARD1 mRNA and protein. Low‐level expression of full‐length BARD1 associated with advanced neuroblastoma. In human neuroblastoma cells, attenuating full‐length BARD1 increased proliferation and invasion capacity. In conclusion, we have identified two potentially causative SNPs at the BARD1 locus associated with predisposition to high‐risk neuroblastoma, and have shown that full‐length BARD1 may act as tumor suppressor. Abstract : What's new? BARD1 locus (2q35) has been previously identified as a susceptibility locus of high‐risk neuroblastoma. However, the functional variants at this locus and biological mechanisms accounting for the risk remain largely unknown. Using GWAS data from 556 patients and 2, 575 controls, here the authors begin to unravel the biology of genetic predisposition to high‐risk neuroblastoma due to common variation at the BARD1 gene locus. They provide evidence that at the same locus coexist functional SNPs that independently contribute to the risk of neuroblastoma development and may affect different BARD1 isoforms. Furthermore, they show that full‐length BARD1 may act as tumor suppressor.